Pravni vidiki politike in gospodarstva - Šinkovec, Janez (Teorija in praksa, 2000)
In the introduction the author defines the term politics and political pettifoggery and reviews a development of relationship between economy and the state. The foundation for the relations is in freedoms defined in Slovene constitution, therefore the author draws attention to theirs interpretation. Interference in entrepreneurial rights has to be interpreted by constitutional freedoms taking into account relation between public and private interest; action has to be estimated with regard to the legal consequences; interfering in the rights is limited to the law only and this isbased on the principle of power division. Special attention is given to the laws of action characteristic for the periods of crises, and in our context for the transitional period. A particularity in limiting entrepreneurial rights is explained by German 'level theory', with traditional objective and subjective limitations, with tax interference and giving often controversial subsidy. Introduction of rational law, simulation of regulation at passing acts, principle of proportionality and caution at using undetermined notions and free consideration are suggested in order to improve the situation in law. At the end the author frames some suggestions for improving the situation in jurisdiction.
Keywords: politics; politika; politizacija; politična ekonomija; economy; gospodarstvo; pravno varstvo; gospodarsko pravo; podjetja; podjetništvo; state; država; pravo; law; ustave